PENGARUH KEPEMIMPINAN KEPALA SEKOLAH, KINERJA GURU DAN SUPERVISI PENGAWAS TERHADAP MUTU PEMBELAJARAN SEKOLAH MENENGAH PERTAMA DI KABUPATEN BANGKA SELATAN - Hamdan Hamdan; Dwi Utomo; Afrizal Afrizal (JEM Jurnal Ekonomi dan Manajemen, 2022)
This study aims to determine and analyze the influence of principals' leadership, teacher performance, and supervision on the quality of junior high school learning in the South Bangka Regency. The type of data used in this study is primary data, by distributing questionnaires to respondents consisting of principals, teachers, and supervisors. The research data were analyzed using multiple regression techniques. The results of the study concluded that simultaneously there was a positive and significant influence on the principal's leadership, teacher performance, and supervision on the quality of learning, and there was a positive and significant influence on the principal's leadership on the quality of learning. There is a positive and significant effect of teacher performance on the quality of learning. There is a positive and significant effect of supervision on the quality of learning. In improving the quality of learning, it is necessary to carry out a measurable assessment with the right indicators so that the decisions taken are on target.